The Teachers' Efforts in Forming Social Competence of Sixth Grade Students of Elementary Schools in Sungai Ambawang - Mardiyah Mardiyah (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
This study is titled Teachers' Efforts in Forming Social Competence of Grade 6 Students of 36 Primary Schools in Sungai Ambawang, Kubu Raya Regency. The problems studied are 1). How is the teacher's effort in shaping the social competence of grade 6 students of 36 Ambawang River elementary schools in schools? 2). How is the teacher's effort in shaping the social competence of grade 6 students of 36 Ambawang River elementary schools at home? 3). Are there any inhibiting factors in teacher efforts in shaping the competence of grade 6 students at 36 elementary schools in Sungai Ambawang? The method used is descriptive qualitative, using participant observation, interviews, and documentation of research instruments. The sample of this study was seven students, five people in sixth grade, and 2 in fifth class. The findings of this study explained that the efforts of teachers, students in grades 6 and 5 in the effort to establish social competence had been carried out well, but it hasn't been held maximally. Social Competence of students is medium and well-formed, but a small number of others still have problems in terms of time and willingness to enter challenging conditions in a particular social situation.